Levels of Digital Inequality and The Process of Adaptation to Digital Culture - Ali Şimşek; Furkan Sürün (Medya ve Kültür)
Digital inequality refers to the differences in individuals' access to, use of and benefits from digital technologies. This study aims to explore the effects of demographic differences on digital cultural inclusion and exclusion. The study is designed using a sequential mixed model. The population of the study is consisted of individuals over the age of 18 living in the Sakarya province of Turkey. The survey form was administered to collect data from 504 participants selected from the population by random sampling. Semi-structured interviews were carried out with 8 participants who are considered capable of providing detailed information on the subject. The survey form contained statements intended to measure the access and benefit levels of the participants. The usage frequency is discussed via questions prepared by the researcher based on the Likert scale, considering the sub-dimensions of digital citizenship introduced by Mike Ribble. According to the results, the participants' access to digital technologies is at high level. Concerning digital technology usage, differences are primarily determined on the basis of the age factor. With regard to the level of benefits, the satisfaction level increased as the education level increased and age decreased. Results obtained through interviews suggested that using digital technologies activated those involved in this digital culture, made their lives easier, and allowed them to engage in popular issues. Finally, the participants thought that the activities in the new media helped them engaging in current events and get important news to cope with recent events and discussions.